Financial Analysis on the Bank Finances to Small Scale Industries in Erode District in Tamil Nadu - Mr.E.Manikandan; Dr.C.Sengottuvel (Zien Journals, 2021)
Finance is an important input for an industry. For a small scale industry the need for finance is very essential due to its limited resources. The sources of finance for small scale industries are of two typesinternal and external. The role of commercial banks in the process of economic development is well recognized. The year 1969 was a major turning point in Indian financial systems when 14 major banks were nationalized. Different national and state level institutions operating in the country for meeting the credit requirements of the SSIs sector include Small Industries Development Bank of India, Commercial Banks, Regional Rural Banks, Co-operative Banks (State, Central and Primary), State Financial Corporations/ State Industrial Investment Corporations, State Small Industries Development Corporation, National Bank for Agriculture and Rural Development, statutory bodies (KVIC, COIR Board, Handloom Board and Handicraft Boards), National Small Industries Corporations Limited and the like. The State bank of India lending to the small-scale industries in Erode district, compared to the public sector and the priority sector lending. The trend values showed that the target has increased faster than the actual number of advances. The recovery rate of the SSI advances is a maximum of 72% in Erode district.
Keywords: commercial; process; economic; development